Stakhanov movement in the forestry industry: practices of regional meetings - Zykin, Ivan V. (Journal of the Belarusian State University. History, 2026)
The formulation of the Stakhanov movement in the Soviet Union, which quickly received comprehensive support from party and government bodies in the mid-1930s, was impossible without a system of events (meetings, rallies, conferences). This system encompassed all levels of government and the economy, branches of industries, and categories of workers. In the forestry industry, which employed between 1.5 and 2.0 mln workers at various times, considerable attention was paid to the development of the Stakhanov movement in timber procurement, the supply of raw materials for enterprises depending on its results. The materials of regional meetings are analysed, demonstrating the transformation of the views of various categories of workers on the Stakhanov movement in the second half of the 1930s. It is revealed that the transcripts of events contain sharp criticism of the problems of the forestry industry and a broad list of Stakhanovite demands, whereas newspapers reported primarily on achievements and, in a more nuanced manner, on problems. A common theme among the meetings was the contrast between the collective «we» of party and government officials and business leaders with the individualism of the Stakhanovites, who quickly grasped the benefits of the new form of socialist competition. It was noted that participation in meetings, rallies, and conferences, where they could share successes and gain useful information about working methods, was a motivating factor for the Stakhanovites. It was concluded that with the strengthening of problem-motivational messages during the work of party congresses and conferences or after the publication of government decrees on the work of the forestry industry, there was a gradual replacement of events of a ceremonial, mobilisation focus with meetings to discuss production problems.